Digitalisasi Pajak dan Etika Syariah: Integrasi Nilai Islam dalam Reformasi Pajak Modern di Indonesia - Fathmah Hanum; Lilik Rahmawati (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
Indonesia's tax system is undergoing major changes as a result of the development of digital technologies. However, in order for fiscal policy to be focused on social justice, this modernization necessitates not just technological competence but also the integration of moral and spiritual principles. With an emphasis on the duties and moral obligations of system management stakeholders (supervisors, IT professionals, and field managers), this study attempts to examine how Sharia ethical concepts are incorporated into tax digitalization. This study investigates the connection between Islamic economic values like justice (al-'adl), reliability, and transparency with the current practice of tax digitization using a qualitative descriptive analysis approach and literature. The study's conclusions show that incorporating sharia principles is essential for encouraging administrators' moral and spiritual integrity, which will boost public confidence and increase taxpayer compliance. A digital system that guarantees open data flow and real-time accountability at every level, from reporting to fund utilization, based on the administrators' credibility, achieves the necessary transparency. Therefore, tax digitization is a way to realize public benefit through a synergy between spiritual values and technology, which requires fiscal system implementers to uphold high ethical standards.